A time to change direction - Colfer, C.J.P.; Prabhu, R. (Routledge, 2023)
Colfer and Prabhu build on concerns highlighted in the Glasgow Leaders Declaration on Forests and Land Use, recognizing the ‘wickedness’ of climate change and other problems bedeviling the Earth and its peoples. This chapter, in response, argues for the use of collaborative, bottom-up approaches where learning and adaptation are central features. These authors build on the longitudinal experience – some of two decades or more – of multiple teams of researchers who have worked at the community level using the ACM approach and highlighting their many enduring accomplishments. After a brief history of the collection’s development, Colfer and Prabhu argue for expanding these same kinds of processes (collaboration, learning) upward and outward. Rather than urging a substitution of large-scale action over community work, they argue for stronger links among micro, meso, and macro levels. The chapter also weaves an introduction to the book’s chapters into four topics of great importance in addressing environmental issues: (1) multiple scales and the exercise of power, (2) the value of excellent facilitation and learning, (3) collaboration in multistakeholder forums, and (4) inclusivity and intersectionality. The chapter concludes by identifying ways forward at the community and broader scales.